1997
DOI: 10.1073/pnas.94.10.5095
|View full text |Cite
|
Sign up to set email alerts
|

The subcellular localization of E2F-4 is cell-cycle dependent

Abstract: The E2F family of transcription factors plays a crucial role in cell cycle progression. E2F activity is tightly regulated by a number of mechanisms, which include the timely synthesis and degradation of E2F, interaction with retinoblastoma protein family members (''pocket proteins''), association with DP heterodimeric partner proteins, and phosphorylation of the E2F͞DP complex. Here we report that another mechanism, subcellular localization, is important for the regulation of E2F activity. Unlike E2F-1, -2, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
170
6
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(195 citation statements)
references
References 42 publications
(40 reference statements)
17
170
6
2
Order By: Relevance
“…Alternatively, the strong proliferative block provided by p16 in these astrocytomas may generate a strong signal for the nuclear compartmentalization of E2F-4. The latter possibility would be consistent with the previously described, cell cycle dependent compartmentalization of this particular E2F-family member (Lindeman et al, 1997).…”
Section: Discussionsupporting
confidence: 91%
“…Alternatively, the strong proliferative block provided by p16 in these astrocytomas may generate a strong signal for the nuclear compartmentalization of E2F-4. The latter possibility would be consistent with the previously described, cell cycle dependent compartmentalization of this particular E2F-family member (Lindeman et al, 1997).…”
Section: Discussionsupporting
confidence: 91%
“…This abnormal cytoplasmic localisation in the malignant cells might reflect gene mutation, posttranscriptional modification or abnormal phosphorylation of its protein in breast cancer and needs further investigation. In addition, we found that E2F-4 was expressed in both the nuclei and cytoplasm of the normal and malignant mammary epithelial cells, in agreement with Lindeman et al 66 who reported both nuclear and cytoplasmic expression of E2F-4. We also found that the nuclear overexpression of E2F-4 was associated with higher-grade tumours and positive lymph node disease, which may suggest an oncogenic rather than a tumour suppressor role in breast cancer.…”
Section: C) Telomeric Repeat Binding Factor-2supporting
confidence: 92%
“…To test this possibility, we transfected into satellite-cell derived myotubes a plasmid encoding an E2F-4 chimeric protein carrying a nuclear localization signal (E2F-4-NLS) (Muller et al, 1997). The NLS ensures that the protein is carried into the nucleus, since wild type E2F-4 is cytoplasmic (Magae et al, 1996;de la Luna et al, 1996;Lindeman et al, 1997;Muller et al, 1997;Verona et al, 1997). Similar to the other E2Fs, E2F-4-NLS did not activate S phase in myotubes (data not shown).…”
Section: E2f Does Not Activate Dna Synthesis In Td Myotubesmentioning
confidence: 85%